Pengaruh Layanan Bimbingan Kelompok Dalam Meningkatkan Kemandirian Siswa Menyelesaikan Masalah Belajar - Azmatul Khairiah Sari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
This article discusses about autonomy to solve their learning problem. The students need a autonomy to solve their learning problem. Group guidance can be used to improve autonomy to complete the learning problem. This research was aimed at disclosing the influence of group guidance service to improve autonomy to solve the learning problem. An experimental research pretest and posttest control group design was utilized to test whether group guidance can better improve autonomy to complete the learning problem. The findings of this research were: (1) there is a significant difference between post test and pre-test of the experiment group on autonomy to complete the learning problem. (2) there is no difference on the pre and post test of the control group students on autonomy to complete the learning problem. (3) there is a significant difference on autonomy to complete the learning problem between experiment group and control group.